O-Acetyl-GD2 as a Therapeutic Target for Breast Cancer Stem Cells - Cheng, Jing-Yan; Hung, Jung-Tung; Lin, Juway; Lo, Fei-Yun; Huang, Jing-Rong; Chiou, Shih-Pin; Wang, Ya-Hui; Lin, Ruey-Jen; Wu, Jen-Chine; Yu, John; Yu, Alice L. (Frontiers in Immunology, 2022)
Cancer stem cells (CSCs) that drive tumor progression and disease recurrence are rare subsets of tumor cells. CSCs are relatively resistant to conventional chemotherapy and radiotherapy. Eradication of CSCs is thus essential to achieve durable responses. GD2 was reported to be CSC marker in human triple negative breast cancer, and anti-GD2 immunotherapy showed reduced tumor growth in cell lines. Using a specific anti-OAcGD2 antibody, mAb8D6, we set out to determine whether OAcGD2+ cells exhibit stem cell properties and mAb8D6 can inhibit tumor growth by targeting OAcGD2+CSCs. Method OAcGD2 expression in patient-derived xenografts (PDXs) of breast cancer was determined by flow cytometric analyses using mAb8D6. The stemness of OAcGD2+ cells isolated by sorting, and the effects of mAb8B6 were assessed by CSC growth and mammosphere formation in vitro and tumor growth in vivo using PDX models. Result We found that the OAcGD2 expression levels in six PDXs of various molecular subtypes of breast cancer highly correlated with their previously defined CSC markers in these PDXs. The sorted OAcGD2+ cells displayed a greater capacity for mammosphere formation in vitro and tumor initiation in vivo than OAcGD2- cells. In addition, the majority of OAcGD2+ cells were aldehyde dehydrogenase (ALDH+) or CD44hiCD24lo, the known CSC markers in breast cancer. Treatment of PDXs-bearing mice with mAb8B6 but not doxorubicin, suppressed the tumor growth, along with reduced CSCs as assessed by CSC markers and in vivo tumorigenicity. In vitro, mAb8B6 suppressed proliferation and mammosphere formation, and induced apoptosis of OAcGD2+ breast cancer cells harvested from PDXs, in a dose-dependent manner. Finally, administration of mAb8B6 in vivo dramatically suppressed tumor growth of OAcGD2+ breast CSCs (BCSCs) with complete tumor abrogation in 3/6 mice. Conclusion OAcGD2 is a novel marker for CSC in various subtypes of breast cancer. Anti-OAcGD2 mAb8B6 directly eradicated OAcGD2+ cells and reduced tumor growth in PDX model. Our data demonstrate the potential of mAb8B6 as a promising immunotherapeutic agent to target BCSCs.